"It's business as usual": adolescents perspectives on the ban of alcohol sachets towards reduction in under age alcohol use in Malawi - Sangwani Salimu; Alinane Linda Nyondo-Mipando (BMC, 2020)
Abstract Background Alcohol contributes to poor health, social and economic outcomes among adolescents. In Malawi, alcohol consumption among young people significantly increased after the introduction of alcohol sachets. A government ban on the sale of alcohol sachets affected in 2012 aimed to reduce prevalence of alcohol among users. We explored adolescents perceptions regarding the effectiveness of the ban towards reducing alcohol consumption among the under aged in the country. Methods Using a descriptive phenomenological school-based approach, we recruited 44 school-going adolescents, 15-17 year olds using snow ball sampling and conducted 12 individual semi-structured interviews and four group discussions differentiated by sex. We sought a waiver from College of Medicine Ethics Committee (COMREC) to obtain verbal consent from adolescents. All interviews and discussions were digitally recorded and simultaneously transcribed and translated verbatim into English. Data management and analysis was done manually using thematic approach. Results Aggressive packaging, and marketing tendencies and lack of restrictive measures in Malawi have rendered the ban ineffective through increased affordability and availability to different income population groups and the underage. Results indicate that even though adolescents perceive the ban as a significant step towards reducing under age alcohol use, personality and drinking motives precede any interventions. Adolescents emphasized on strong personality as a significant factor for reduced alcohol intake or abstinence. Conclusions We recommend strict alcohol policy and enforcement regarding packaging, pricing, positive role modelling by parents and enhanced adolescent personality development through schools and families.